Bangladesh in the rapid alert system for food and feed notifications in the period 2000-2012: A review - Alam, Nazmul (Ceska Akademie Zemedelskych Ved * Ustav Zemedelskych a Potravinarskych Informaci, 2013)
Information provided in the Rapid Alert System for Food and Feed (RASFF) portal database of the European Commission on "crustaceans and products thereof" for Bangladesh during 2000-2012 was investigated to analyse the trends of occurrences. A total of 159 (10.56%) notifications (alert -- 40; border rejection -- 47; information -- 72) were recorded for Bangladesh against a worldwide 1505 notifications. During the period 120 (20.27%) notifications were identified for residue of veterinary medicinal products against 592 notifications recorded in the portal. Forty-eight consignments were re-despatched to Bangladesh while 11 consignments were destroyed at the European border as a consequence of the notifications by the European countries.